The reciprocal relationships between Chinese children’s perception of interparental conflict, negative thinking, and depression symptoms: A cross-lagged study - Yang, Meirong; Meng, Zhaoyan; Qi, Huan; Duan, Xiangfei; Zhang, Libin (Frontiers in Psychology, 2022)
The present longitudinal study used the traditional cross-lagged panel model (CLPM) and autoregressive latent trajectory model with structured residuals (ALT-SR) to examine the relationships between perceived interparental conflict, negative thinking, and depression symptoms in Chinese children. Changes in these three variables over time were also examined, as well as the trait and state aspects of the relationships between them. A sample of 516 third-grade primary students completed questionnaires about interparental conflict, negative thinking, and depression three times over a period of 1 year, at six-month intervals. The CLPM findings indicated that, assuming that stability of each variable across time was controlled, Chinese children’s perception of interparental conflict significantly affected their level of depression through the mediating path of negative thinking. After taking trait factors into account, among all the significant autoregressive and cross-lagged paths originally found in the CLPM, only one third remained significant in the ALT-SR model. More specifically, the ALT-SR model, revealed a driving effect of children’s negative thinking on perceived interparental conflict and depression symptoms. The CLPM model although elucidated the interplay among three variables, the ALT-SR model showed little evidence of their interrelated growth across time. Taken together, these results indicate that children’s perceived interparental conflict in the long term are a stable trait, with few state-level fluctuations, and is not a significant within-person predictor of subsequent children’s internalization problems. These perceptions appear to contribute more to children’s general psychological tendency than do changes over time. The research is the first to test the reciprocal relationships between Chinese children’s perceived interparental conflict, negative thinking, and depression symptoms. The study contributes to our understanding of that extend previous results and have implications for complementary theoretical and practical interventions. The complementary techniques of CLPM and ALT-SR models offer different insights into children’s internalization problems, and hold promise for supporting the building of more comprehensive children’s developmental theories that acknowledge the interconnectedness of different domains of mental health.